Removal of Perfluorooctanoic Acid and Microcystins from Drinking Water by Electrocoagulation - Stephen Opoku-Duah; Dennis Johnson (Journal of Chemistry)
Perfluorooctanoic acid (PFOA) and microcystins are some of the well-known chemical contaminants in drinking water in the USA. Despite the availability of filtration technologies like ion-exchange resins, activated-carbon, and high-pressure membrane filters, these contaminants still remain widespread in the environment. In the present study, two innovative aspects of electrocoagulation techniques were tested, (a) cheap and easy-to-operate field-unit instead of hi-tech electrocoagulation and (b) reverse-polarity instead of conventional polarity, and applied to remove PFOA and microcystins from drinking water sources. The method presented here outperformed commercial activated-carbon filtration by nearly 40%. When the efficiency of electrocoagulation was examined in terms of voltage discharge, pH, and reverse-polarity, the results averaged 80% decontamination for individual treatment, while their combined effects produced 100% detoxification in 10–40 minutes, exceeding recently published results. The method shows great economic promise for water and wastewater treatment and chemical recycling.